Pyridylpyrrolido ligand in Ge(II) and Sn(II) chemistry: synthesis, reactivity and catalytic application - Pahar, Sanjukta; Sharma, Vishal; Tothadi, Srinu; Sen, Sakya S. (Dalton Transactions, 2021)
In our previous communication, we have reported the synthesis of a new chlorogermylene (B) featuring a pyridylpyrrolido ligand. This study details the preparation of a series of new germylenes and stannylenes starting from B. A transmetallation reaction between B and SnCl2 led to the analogous chlorostannylene (1) with the simultaneous elimination of GeCl2. This is a very unusual example of transmetallation between two elements of the same group. The preparation of 1via lithiation led to the formation of 2 as a side product, where the ortho C-H bond of the pyridine ring was activated and functionalized with a Bu-n moiety. Subsequently, B and 1 were used as precursors to generate germylene (4) and stannylene (5) featuring tris(trimethylsilyl)silyl (hypersilyl) moieties. We also prepared tetrafluoropyridyl germylene (6) by reacting 4 with C5F5N with the simultaneous elimination of (Me3Si)(3)SiF by utilizing the fluoride affinity of the silicon atom. As there is scarcity of Sn(II) compounds as single-site catalysts, we investigated 5 as a catalyst towards the hydroboration of aldehydes, ketones, alkenes and alkynes. All the compounds have been characterized by single-crystal X-ray diffraction and by state of the art spectroscopic studies.

Reactivities of silaimines with boranes: from cooperative B-H bond activation to donor stabilized silyl cation - Bisai, Milan Kumar; Sharma, Vishal; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2021)
The recently published silylene with a tris(trimethylsilyl) group, PhC(NtBu)(2)SiSi(SiMe3)(3) (1), was reacted with the organic azides such as SiMe3N3 and AdN(3) to form the respective hypersilylsilaimines, PhC(NtBu)(2)Si(=NR)Si(SiMe3)(3) 2 (R = SiMe3) and 3 (R = Ad). The B-H bond of HBpin or HBcat was split across the Si=N bond upon reaction with 2, which generated 4 and 5, respectively. However, we could not obtain the crystals of 4 and 5 appropriate for X-ray diffraction. Subsequently, we performed the analogous reactions with a related silaimine PhC(NtBu)(2)Si(=NSiMe3)N(SiMe3) 2 (2') and isolated similar B-H bond activated products 6 and 7. The reaction of 2' with HBCl2 resulted in donor stabilized silyl cations (8 and 9) supported by an amidinate ligand.

Monomeric magnesium catalyzed alkene and alkyne hydroboration - Kumar, Rohit; Dutta, Sayan; Sharma, Vishal; Singh, Praval P.; Gonnade, Rajesh G.; Koley, Debasis; Sen, Sakya S. (Chemistry-A European Journal, 2022)
In this work, two monomeric magnesium alkyl complexes (1 and 2) were prepared using bis(phosphino)carbazole framework and among them 1 has been used as a catalyst for hydroboration of alkenes and alkynes with pinacolborane (HBpin). A broad variety of aromatic and aliphatic alkenes and alkynes were efficiently reduced. Anti-Markovnikov regioselective hydroboration of alkenes and alkynes was achieved, which was confirmed by deuterium-labelling experiments. The work represents the first example of the use of magnesium in homogeneous catalytic hydroboration of alkene with broad substrate scope. Experimental mechanistic investigations and DFT calculations provided insights into the reaction mechanism. Finally, the hydroboration protocol was extended to terpenes.
Keywords: carbazole; Magnesium; monomeric complexes; phosphorous; X-ray Structure

Tridentate NacNac stabilized tin and nickel complexes: access to a monomeric nickel hydride and its catalytic application - Pahar, Sanjukta; Sharma, Vishal; Mahata, Biplab; George, Christy P.; Sharma, Himanshu; Vanka, Kumar; Sen, Sakya S. (Inorganic Chemistry, 2022)
The transmetalation reaction of picolyl-supported tridentate nacnac germylene monochloride [2,6-iPr2-C6H3NC-(Me)CHC(Me)NH(CH2py)]GeCl (1) (py = pyridine) with SnCl2 results in an analogous stannylene chloride (2). The three -coordinated stannylenium cation [{2,6-iPr2-C6H3NC(Me)CHC-(Me)NH(CH2py)}Sn]+ with SnCl3- as a counteranion (3) has been generated through the abstraction of chloride ligand from 2 using an additional equivalent of SnCl2. Instead of forming a donor-acceptor complex, 2 undergoes a facile redox trans-metalation reaction with Ni(COD)2 (COD = cyclooctadiene) and CuCl to afford analogous nickel and copper complexes [2,6-iPr2-C6H3NC(Me)CHC(Me)NH(CH2py)]MCl [M = Ni (4) and Cu (5)]. The reactions of 4 with potassium tri-sec-butylborohydride (commonly known as K-selectride) and AgSbF6 provide access to monomeric Ni(II) hydride, [2,6-iPr2-C6H3NC(Me)CHC(Me)NH(CH2py)]NiH (6) and a Ni(II) cation, [{2,6-iPr2- C6H3NC(Me)CHC(Me)NH(CH2py)}Ni][SbF6] (7), respectively. 6 was found to be an effective catalyst for the hydroboration of amides.

Well-defined calcium compound catalyzes trimerization of arylisocyanates into 1,3,5-triarylisocyanurates - Kumar, Rohit; Sharma, Vishal; Jain, Shailja; Sharma, Himanshu; Vanka, Kumar; Sen, Sakya S. (ChemCatChem, 2022)
We report the synthesis of a calcium complex (2) bearing a tetradentate monoanionic ligand with a diaminoethane core and phenolate and pyridine peripheral donors. Single crystal X-ray studies on 2 revealed that LiI was also co-crystallized, leading to a four-membered ring with four different elements. 2 was found to be an efficient catalyst for the cyclotrimerization of a variety of aromatic isocyanates under mild conditions.
Keywords: calcium; Cyclotrimerization; Isocyanurates; Tetradentate ligand

Controlled reduction of isocyanates to formamides using monomeric magnesium - Kumar, Rohit; Sharma, Vishal; Banerjee, Subhrashis; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2023)
This work describes a transition metal-free methodology involving an efficient and controlled reduction of isocyanates to only formamide derivatives using pinacolborane (HBpin) as the hydrogenating agent and a bis(phosphino)carbazole ligand stabilized magnesium methyl complex (1) as the catalyst. A large number of substrates undergo selective hydroboration and give exclusively N-boryl formamides.

Tridentate NacNac tames T-shaped nickel(I) radical - Pahar, Sanjukta; Sharma, Vishal; Raj, K. Vipin; Sangole, Mayur P.; George, Christy P.; Singh, Kirandeep; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemistry- a european journal, 2024)
The reaction of a nickel(II) chloride complex containing a tridentate beta-diketiminato ligand with a picolyl group [2,6-iPr2-C6H3NC(Me)CHC(Me)NH(CH2py)]Ni(II)Cl (1)] with KSi(SiMe3)3 conveniently afforded a nickel(I) radical with a T-shaped geometry (2). The compound's metalloradical nature was confirmed through electron paramagnetic resonance (EPR) studies and its reaction with TEMPO, resulting in the formation of a highly unusual three-membered nickeloxaziridine complex (3). When reacted with disulfide and diselenide, the S-S and Se-Se bonds were cleaved, and a coupled product was formed through carbon atom of the pyridine-imine group. The nickel(I) radical activates dihydrogen at room temperature and atmospheric pressure to give the monomeric nickel hydride. A thermally stable, T-shaped, nickel(I) radical was straightforward obtained by reduction of a tridentate nacnac nickel(II) chloride with KSi(TMS)3. The metalloradical character of the compound was demonstrated by the formation of a highly unusual nickeloxaziridine complex upon addition of TEMPO. The Ni(I) species displays a rich chemistry towards activation S-S, and Se-Se bond leading to unusual C-C coupled product as well as dihydrogen activation at room temperature and atmospheric pressure to generate monomeric nickel hydride.+image
Keywords: C-C Bond formation; Hydrogen Activation; Metalloradical; Nickel; Tridentate nacnac

Magnesium-ligand cooperation in breaking the O-H and C-H bonds of water and diazoalkane - Sharma, Vishal; Dash, Soumya Ranjan; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2025)
In our previous paper, we reported that the reaction of a tridentate nacnac ligand with a pendant picolyl group, with KHMDS and MgI2, resulted in the formation of a homoleptic hexacoordinate magnesium compound. Here, we show that the analogous reaction of the ligand with CH3MgBr led to a heteroleptic magnesium bromide species (1). Attempts to generate the magnesium hydride species from 1 led to the dearomatization of the pyridine ring, and the resulting product was a magnesium hydroxide (3) presumably generated due to an adventitious amount of water. The reaction of the ligand with nBu2Mg afforded a unique dearomatized magnesium species (2) in high yield. Theoretical calculations reveal the presence of a nonbonding orbital on the magnesium, susceptible to nucleophilic attack. Indeed, the reaction of 2 with H2O/D2O cleaves the O-H/D bond via magnesium-ligand cooperation and generates a magnesium hydroxide (4 and 5). In addition, 2 reacts with Me3SiCHN2 and cleaves the C-H bond to generate another unusual, well-defined magnesium compound with a bridging isocyanide moiety (6) via migration of the SiMe3 group from the carbon to the nitrogen atom. The latter can be described as a dimer of magnesium isocyanamide. DFT calculations were performed to understand the electronic structures of the synthesized molecules.